Liquidity, Monetary Policy, and the Financial Crisis: A New Monetarist Approach - Williamson, Stephen D (American Economic Review, 2012)
A model of public and private liquidity integrates financial intermediation theory with a New Monetarist monetary framework. Non-passive fiscal policy and costs of operating a currency system imply that an optimal policy deviates from the Friedman rule. A liquidity trap can exist in equilibrium away from the Friedman rule, and there exists a permanent nonneutrality of money, driven by an illiquidity effect. Financial frictions can produce a financial-crisis phenomenon that can be mitigated by conventional open market operations working in an unconventional manner. Private asset purchases by the central bank are either irrelevant or they reallocate credit and redistribute income. (JEL E13, E44, E52, E62, G01)